Pelatihan TikZ dalam Pemodelan Directed Multigraph untuk Visualisasi Variasi Jalur Transisi Markov Chain - Alfi Maulani; Andri Sofyan Husein (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2026)
Markov Chain modeling using directed multigraphs is often difficult to visualize because multiple edges represent different transition paths leading to the same state. This community service activity aimed to improve participants' ability to visualize directed multigraphs using TikZ for Markov Chain modeling. The program was conducted through a workshop and hands-on training at Bima International University (UNBIM) MFH Mataram, involving 2 lecturers and 28 students. The training covered transition table construction, domain–codomain identification, and TikZ coding techniques for graph visualization. Evaluation was carried out by comparing participants' practical outputs before and after the training based on graph structure accuracy, multiple-edge representation, and visualization quality. The results showed that 93.3% of participants successfully produced correct directed multigraph visualizations, while TikZ coding skills increased by 81.6%. The training effectively enhanced participants' competence in developing accurate, systematic, and professional Markov Chain visualizations to support mathematics and statistics education.